Understanding Carok in Madura: Legal Reform from Criminal Law and Islamic Law Perspective - Haris Haris; Sholahuddin Al-Fatih; Muhammad Nur (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
This article aimed to describe Carok nowadays from the perspective of criminal law and Islamic law. Carok is a traditional sort of vengeance or conflict seen in specific parts of Indonesia, particularly Madura, East Java. It usually consists of armed battles between groups or people, often resulting from long-standing feuds or disputes over land, honour, or revenge. Carok episodes can be violent and even fatal, and they are firmly ingrained in local cultural and social dynamics. A feeling of honour and pride frequently drives conflicts, and they can be difficult to resolve through normal legal processes. Carok was well-known for the Madurese killing (maybe similar to Hara-kiri in Japan, Sati in India, and so on), which moved on from the beginning as honour killing to nowadays as criminalization. This article intends to conduct legal research, similar to socio-legal research, due to the experience of the author(s) as Madurese, and involving several native Madurese people and figures in the research, such as religious leaders and law enforcers. As a result, this article found that Carok nowadays has identical meanings and punishment in Indonesian criminal law and Islamic law.